PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN DASAR-DASAR DESAIN KOMUNIKASI VISUAL KELAS X DI SMK TEKNOLOGI PLUS PADANG - Chelsy Putri; Adlia Alfiriani; Bernediv Nurdin (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
The problem in this study is the lack of media in learning which makes students easily bored and difficult to understand the material during learning, therefore it is necessary to add learning media as a medium that can help teachers as an implementation of the independent curriculum in delivering material and increasing the grasp of students. The purpose of the study was to determine the use of android-based learning media in Foundations of Visual Communication Design subjects at SMK Teknologi Plus Padang using the MIT App Inventor application. To produce android-based learning media in Foundations of Visual Communication Design subjects at SMK Teknologi Plus Padang using the MIT App Inventor application that is valid. To produce android-based learning media in Foundations of Visual Communication Design subjects at SMK Teknologi Plus Padang using the MIT App Inventor application which is practical. The research method used is Research and Development (RD) with the ADDIE development model.The results of this study show that the average value of the media expert validation test by the validator is 88% with the very valid category, the material validation is 86% with the very valid category. The teacher's practicality test was 85% with the very practical category, and the student practicality test was 87%with the very practical category. The conclusion based on the data obtained from android-based learning media is suitable for use as a learning medium.